2010
DOI: 10.1111/j.1548-1395.2010.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Authority and Preschool Disputes: Learning to Behave in the Classroom

Abstract: Conflict is commonplace in teacher‐centered preschool classroom activities. It is negotiated both verbally and nonverbally, often fading rather than resolving in the interactive moment. The teacher or aide steps in to define what is right and wrong, thus acting to mediate conflict and taking up the position of moral authority. When she does not step in, children may invoke her authority in this regard. Children have a variety of responses to teachers' judgments. When children disagree with teacher/aide's asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In various cultural contexts, children's peer disputes and play conflicts are something that educators treat as requiring intervention and conflict mediation (Bateman, 2015;Karlsson, 2018;Burdelski, in press;Moore, in press;LeMaster, in press). Children themselves have been shown to use numerous discursive and embodied strategies to recruit adults to mediate in their disputes with peers (Danby & Baker, 1998;Cekaite, 2012;LeMaster, 2010;Bateman, 2015;Burdelski, in press). As demonstrated in several studies, children orient towards educators as a moral authority and can threaten each other with teachers' attention (see also Church & Hester, 2012, on children's threats in disputes).…”
Section: Peer-group Cultures Social and Moral Orders In Preschoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In various cultural contexts, children's peer disputes and play conflicts are something that educators treat as requiring intervention and conflict mediation (Bateman, 2015;Karlsson, 2018;Burdelski, in press;Moore, in press;LeMaster, in press). Children themselves have been shown to use numerous discursive and embodied strategies to recruit adults to mediate in their disputes with peers (Danby & Baker, 1998;Cekaite, 2012;LeMaster, 2010;Bateman, 2015;Burdelski, in press). As demonstrated in several studies, children orient towards educators as a moral authority and can threaten each other with teachers' attention (see also Church & Hester, 2012, on children's threats in disputes).…”
Section: Peer-group Cultures Social and Moral Orders In Preschoolsmentioning
confidence: 99%
“…Rather, this thesis demonstrates that these young children had a rich knowledge of the institutional social and moral expectations and responsibilities; for example, the educators' institutional responsibility to attend to crying. Moreover, the children displayed their knowledge of how to use crying for their own social purposes in order to attract an educator's attention and recruit the adult for conflict intervention (Danby & Baker, 1998;Cekaite, 2012;LeMaster, 2010;Bateman, 2015;Burdelski, in press. ) Crying served multiple purposes during children's play conflicts.…”
Section: Children's Responses and Orientation Towards Peers' Cryingmentioning
confidence: 99%
“…In short, many studies have shown an imbalance in behavior by gender among students in American classrooms. Often boys speak more than girls, are more likely to call out answers, and be given the floor while girls will get reprimanded for the same behavior, and boys are much more likely than girls to be praised by the teacher for the same behaviors, and have their answers elaborated (Lee ; LeMaster et al ; LeMaster ; Sadker and Sadker ; Swann ).…”
Section: Faculty–student Collaborations With Local Community Preschoolsmentioning
confidence: 99%
“…In a wide range of settings, references to history in the form of remembered norms are an important aspect of these conflicts (Pagliai 2010c). Barbara LeMaster (2010), for example, demonstrated that both adults and children make reference to remembered classroom norms. One child, Kevin, avoids punishment by referencing a separate classroom norm, the teacher's “Shhh”:…”
Section: Across Time and Place: Interdiscursive Historiesmentioning
confidence: 99%
“…](10) Kevin: ((turns and meanly looks at the aide and raises his index finger to his lips)) Shhhh! [LeMaster 2010:174]…”
Section: Across Time and Place: Interdiscursive Historiesmentioning
confidence: 99%